Motivasi Pendidikan Dalam Retorika Dakwah Lora Thohir - Suud Sarim Karimullah (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2022)
This study looks at the academic motivation in the rhetoric of da'wah carried out by a young Kiai from Madura, namely Lora Thohir. Lora Thohir is very skilled in tongues, entertaining with jokes, brilliant satire with a criticism that aims to build. Then, a qualitative-descriptive approach was used in this study to try to reveal various qualitative information by describing which was carried out carefully and with complete accuracy to provide an accurate and systematic description of a situation. Furthermore, the results of this study state that the da'wah rhetoric carried out by Lora Thohir is more about delivering material that is easy to understand for his congregation contained in persuasive techniques that are interesting from a logical point of view through delivery that is accurate and not confusing for the community who listens to it. Then, the academic motivation in the rhetoric of da'wah carried out by Lora Thohir can be an inspiration that is not only felt by his students but also the general public.